2023
DOI: 10.1037/tra0001303
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and proximal associations among PTSD symptoms, prescription opioid use, and co-use of other substances: Results from a daily monitoring study.

Abstract: Objective: Posttraumatic stress disorder (PTSD) and nonmedical prescription opioid use (NMPOU) are linked. Much of the research documenting this association uses cross-sectional or longitudinal designs that describe patterns of use over extended intervals. The present study used a daily monitoring design to examine how daily fluctuations in PTSD symptoms predicted patterns of prescription opioid use (both medical and nonmedical) and co-use of other substances. This approach has distinct advantages for understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…For other substance use, our results showed no association between using other substances, primarily cocaine and opioids, and subsequent PTSD symptom severity or the likelihood of discontinuing treatment, which is consistent with previous prospective examinations (Badour et al., 2023). Taken together, the present study and existing literature demonstrate mixed findings on the association between alcohol use and PTSD treatment, but the association between other substance use and PTSD treatment outcomes is more uniformly null.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For other substance use, our results showed no association between using other substances, primarily cocaine and opioids, and subsequent PTSD symptom severity or the likelihood of discontinuing treatment, which is consistent with previous prospective examinations (Badour et al., 2023). Taken together, the present study and existing literature demonstrate mixed findings on the association between alcohol use and PTSD treatment, but the association between other substance use and PTSD treatment outcomes is more uniformly null.…”
Section: Discussionsupporting
confidence: 92%
“…(2021) noted that neither substance use (i.e., alcohol, cocaine, marijuana, benzodiazepines, opioids, amphetamines) nor the frequency of use were significant predictors of PTSD symptoms in the next session. The authors also found that opioid use, alone or with other substances, did not predict next‐day PTSD symptoms in a nontreatment study of daily monitoring of use and symptoms (Badour et al., 2023). Overall, some studies have shown a positive concurrent association between alcohol use and PTSD symptoms (Black et al., 2018; Possemato et al., 2015), one study found a prospective increase in PTSD symptoms (Tripp et al., 2020), and another found no association (Badour et al., 2021).…”
mentioning
confidence: 98%
See 1 more Smart Citation